Maraknya Tenaga Kerja Asing Ilegal di Indonesia Sebagai Akibat Lemahnya Pengawasan Ketenagakerjaan - Pranitiaz, Laras Medina; Wibowo, Hanifah Fairuz; Putri, Nasywa Awalia; Dewanti, Tyur Regina; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The existence and increase in the quantity of Foreign Workers (TKA) in Indonesia has given rise to a lot of debate that has spread in society, especially for workers. So that in certain conditions it can actually give rise to various problems, including violations of the residence and work permits of foreign workers, often in their passports it is written that the permission given by the Indonesian government and immigration authorities is for them to work as foreign workers in Indonesia. position and certain period of time, not just as a tourist. The research conducted by the author is a type of normative juridical research. Normative law focuses on legal concepts, principles and legal rules. Normative legal research focuses on positive legal norms such as statutory regulations. Apart from that, in principle this research also comes from secondary legal materials.. The research results show that the influx of foreign workers (TKA) into Indonesia hampers economic growth, reduces employment opportunities, and reduces the wage level of local workers. Law enforcement is carried out by checking, inspecting and providing sanctions for TKA violations. Administrative sanctions in the form of a fine of IDR 6-36 million in accordance with PP No. 34 of 2021. Apart from that, the sanction for illegal foreign workers is in the form of deportation. Preventive and educational efforts are carried out through outreach to companies regarding the rules for employing foreign workers.